PQ4R METHOD ON SHORT STORY READING SKILLS - Audya Dewi Ajeng Kartika; Cholifah Tur Rosidah (Media Inovasi Pendidikan dan Publikasi, 2024)
This research is based on observation results. students' ability to read and understand short stories directly and equipped with data on the average score of student learning outcomes, especially in Indonesian language learning, it was found that students still had difficulty reading the short stories they read. This research employs a pre-experimental approach utilizing a quasi-experimental research design, also known as quasi-experimentation, specifically in the form of a Posttest Only Control Design. The population in this study were classes IVA and IVB with a total of 46 students. The data collection methods in this research are tests and observations. The results of observations regarding the implementation of the PQ4R learning method on reading and understanding short story skills can be said to be effective, this can be seen from the score with an average value of 3.6, included in the very good category. The majority of students are more active in the process of learning short.